EQUALITY VIS-À-VIS AFFIRMATIVE ACTION FROM DIFFERENT PERSPECTIVES - Harlida Abdul Wahab (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2017)
With regard to the position of the Malays, the rationale behind their preferential treatment is more complex. The justification generally is their need for protective discrimination based on the ground that the Malays form an economically depressed community, and that if positive steps are not taken to advance their economic status, it may result in communal strife. The Government faces a daunting task in deciding how to deal with this issue: both continuity and reform carry great dangers, and no solution will gain complete acceptance. This article applies doctrinal legal research and interview where the theory of equality and affirmative action were intensely examined. This article provides an insight to the concept of equality and the operation of affirmative action as provided under the Federal Constitution from different perspectives.